Endogenous Wage Rigidity - Jonas Agell; Helge Bennmarker (Center for Economic Studies and ifo Institute (CESifo), 2003)
We use a random survey of Swedish human resource managers to study the reasons for wage rigidity. Our findings are as follows. First, during the exceptional recession of the 1990s only 1.1 percent of workers received a wage cut. Second, much wage rigidity can be traced to behavioral mechanisms involving negative reciprocity, relative wage comparisons and money illusion. Third, the reasons for wage rigidity differ significantly between large and small establishments, and between the high- and low-end of the labor market. Fourth, there are significant empirical complementarities between efficiency wage mechanisms and worker bargaining strength, and between exogenous institutions and endogenous sources of wage rigidity. Fifth, external pay comparisons are a more important source of rigidity in highly unionized establishments. Sixth, there are significant gender differences in pay bargaining and work moral.
Keywords: 330; wage rigidity; survey evidence; matched data; reciprocity; behavioral macroeconomis; labor law